Philosophy of Materialism and Philosophy of Naturalism - Ayut Nursusanti; Jessica Andriany; Resa Agustina; Arita Wahyuni; Hestia Alika K; Selvi Oktavia (PT FORMOSA CENDEKIA GLOBAL, 2022)
This article looks at the historical materialism approach of Karl Max and naturalism according to J.J Rousseau. Materialism is an understanding that only relies on material that does not believe in what is behind the unseen world. Not believing in the unseen world means not believing in the existence of a power that controls the universe and that automatically denies the existence of God as the creator of the universe, because according to this understanding nature and everything in it originate from one source, namely matter. Marx believed that human intellectual development was determined by the material conditions of human life. That is, material needs precede consciousness. This theory is often called historical materialism. Naturalism is a school that believes in nature and also milieu (environment). The flow of naturalism views that the child created by the creator is good while the environment is bad. Naturalism is a school that believes in nature and also milieu (environment). The flow of naturalism views that the child created by the creator is good while the environment is bad.